Additive Effect of Oral Tetradecanoic Acid to Tamsulosin and Finasteride in a Benign Prostatic Hyperplasia Rat Model (Global Journal of Medical Research, 2020)
We investigated the benefit of the tetradecanoic acid combined with tamsulosin and finasteride, in a benign prostatic hyperplasia (BPH) rat model. By bilateral orchiectomy under ketamine anesthesia Castration was performed. A rat model of BPH was established by daily intramuscular administration of testosterone propionate plus 17 alpha-estradiol for 8 weeks. For 4 weeks from week 6 to 9 post-surgery model rats were administered combinations of 20 mg/kg of tetradecanoic acid, 0.01 mg/kg tamsulosin and 1 mg/kg finasteride once daily by oral gavage. Body and genitourinary organ weights were recorded, serums were assayed for hormone concentrations, and tissues were subjected to histopathology Combined tetradecanoic acid, tamsulosin, and finasteride significantly decreased prostatic index, serum hormone levels, epithelial thickness, The 3-drug combination was more effective than any other combination or tetradecanoic acid alone. These results suggest that tetradecanoic acid addition to tamsulosin and finasteride may be beneficial for the treatment of BPH patients who do not respond to tamsulosin plus finasteride.
Keywords: 5alpha-reductase inhibitor; tetradecanoic acid; tamsulosin; finasteride